KONSELING BERBASIS PESANTREN UNTUK MENINGKATKAN KESEHATAN MENTAL DAN KESEJAHTERAAN PSIKOLOGIS SANTRIWATI BARU - Arifin, Samsul; Yohandi; As'ad (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2024)
The purpose of this study is pesantren-based counseling (da’wah bil-irsyad) for strengthening in increasing the resilience of mental health and psychological well-being of new female santri in child-friendly pesantren. The research method used was action research with a service-learning approach. The results showed the decline in mental health and psychological well-being of new santriwati due to the lack of assistance to improve mental health and psychological well-being with a counseling approach that is extracted from the values of pesantren local wisdom.  The decline in mental health and psychological well-being has an impact on self-growth, less able to manage a new environment, less direction in life, less positive relationships with others, disappointment with oneself, and less autonomy. The actions taken are counseling assistance in the form of studying pesantren local wisdom, training, and making pesantren-based mental health and psychological well-being modules. This research is very useful for new female students and managers of child-friendly pesantren programs as well as the development of mental health and Islamic counseling courses. Keywords: da’wah bil-irsyad, mental health, psychological well-being, santri.